Prevalence, antibiotic and oil resistance pattern of some bacterial isolates from burns - Mona I. Mabrouk, Hoda Hamed El-Hendawy, Amr Mohamad Basha, Neveen Mohamed Saleh (Journal of Applied Pharmaceutical Science, 2016)
Infection is an important cause of mortality in patients with burns. Rapid emergence of hospital pathogens and antibiotic-resistant organisms necessitate periodic evaluation of bacterial colonization patterns and antibiogram sensitivity in burn wards. Sixty isolates from wounds of burns were collected from two hospitals in Cairo, Egypt along the period of 12 months in 2013. Antibiotic sensitivity of these isolates was assessed by single disk diffusion method. Multi drug resistance percentage and the most prevalent resistance phenotype among bacterial isolates were recorded. In addition, 19 essential oils were tested against the MDR isolates. The most potent oils were analyzed by GC-MS to determine their main chemical constituents. According to microbiological and biochemical identification method, Pseudomonas aeruginosa was the most dominant organism 23 (38%), followed by Staphylococcus aureus 16 (27%), Klebsiella spp. 11 (18%), Acinetobacter spp. 4 (7%). Three isolates of Escherichia coli (5%) and three isolates of Proteus spp. (5%). Piperacillin-tazobactam, imipenem and linezolid antibiotics were the most effective antibiotics against Pseudomonas aeruginosa, Enterobacteriaceae and S. aureus isolates respectively. Cinnamon and thyme essential oils were the most potent oils against the multi drug resistant burn wound isolate. Cinnamaldehyde (60.7%) and ρ-cymene (50%) were the major chemical constituents in cinnamon and thyme essential oils, respectively. It is clear that antibiotic resistance levels are high among the examined bacterial isolates of burn wounds. This study could be useful for physician to better choice of empiric therapy. Cinnamon and thyme may be used as a promising an alternative medicine for the treatment of burn wound infections.
Keywords: Burns, wound infection, antibiotic resistance, cinnamon bark, thyme.